Effect of Uric Acid-Lowering Agents on Patients With Heart Failure: A Systematic Review and Meta-Analysis of Randomised Controlled Trials - Xu, Hongxuan; Liu, Yunqing; Meng, Lingbing; Wang, Li; Liu, Deping (Frontiers in Cardiovascular Medicine, 2021)
Background: Elevated serum uric acid (SUA) level is considered an independent predictor of all-cause mortality and the combined endpoint of death or readmission in cardiovascular disease patients. However, the causal relationship between uric acid-lowering therapies (ULTs) and heart failure is still controversial. Design: Meta-analyses were performed to systematically compile available evidence to determine the overall effect of ULTs on heart failure patients. Method: We conducted this systematic review following the PRISMA statement guidelines. Databases were searched to identify randomised controlled trials related to the influence of a ULT intervention in people with heart failure. Data extracted from the included studies were subjected to a meta-analysis to compare the effects of ULTs to a control. Results: Pooled analysis of left ventricular ejection fraction (LEVF) showed an insignificant result towards the ULT group (MD, 1.63%; 95%CI, −1.61 to 4.88; p = 0.32; three studies). Pooled analysis of the 6-Minute Walk Test (6MWT) showed an insignificant result towards the ULT group (MD, 4.59; 95%CI, −12.683 to 22.00; p = 0.61; four studies). Pooled analysis of BNP/NT-pro-BNP led to a nearly statistically significant result towards the ULT group (SMD, −0.30; 95%CI, −0.64 to 0.04; p = 0.08; five studies). Pooled analysis of all-cause mortality and cardiovascular death between ULTs (all XOIs) and placebo did not show a significant difference (RR, 1.26; 95% CI, 0.74 to 2.15, p = 0.39). Conclusion: ULTs did not improve LVEF, BNP/NT-pro-BNP, 6MWT, all-cause mortality, and CV death in heart failure patients. UA may just be a risk marker of heart failure.